2019
DOI: 10.1111/1753-6405.12947
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent abortion in 11 high‐income countries including Australia: towards the establishment of a minimum data set

Abstract: Objective: A major public health challenge in Australia is the lack of national adolescent abortion data. This descriptive study identifies, collates and describes publicly available adolescent abortion data in high-income countries including Australia, to describe trends over 10 years and provide recommendations for strengthening data collection.Methods: Data were extracted from publicly available government sources that met inclusion criteria. All relevant adolescent abortion data from 2007 to 2017 were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Birth rates to teenage mothers are also declining, potentially indicating alternate modes of contraception or other proactive approaches to avoid pregnancy. A decline in adolescent abortion rates was also reported in two Australian states between 2007 and 2017 [38], providing further evidence of a decline in teenage pregnancy rates. Overall, sexual health behaviours showed a negative trend, but sexual health outcomes have improved in terms of birth rates and rates of STIs in recent years (since 2012).…”
Section: Discussionmentioning
confidence: 56%
“…Birth rates to teenage mothers are also declining, potentially indicating alternate modes of contraception or other proactive approaches to avoid pregnancy. A decline in adolescent abortion rates was also reported in two Australian states between 2007 and 2017 [38], providing further evidence of a decline in teenage pregnancy rates. Overall, sexual health behaviours showed a negative trend, but sexual health outcomes have improved in terms of birth rates and rates of STIs in recent years (since 2012).…”
Section: Discussionmentioning
confidence: 56%
“…Abortion remains a relatively common outcome of adolescent pregnancy despite an overall downward trend in abortion incidence among adolescents in HICs [3]. A recent study examined complete adolescent abortion and pregnancy data and found that 17%-69% of pregnancies resulted in abortion [4].…”
Section: Introductionmentioning
confidence: 99%